Analisis perbandingan kinerja keuangan bank syariah dan bank konvensional pada masa pandemi covid-19 - R. Sri Handayani; Nurfitriani Nurfitriani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The Covid-19 pandemic has an impact on the banking sector which affects financial performance, because financing is not running smoothly due to debtor arrears due to many people losing their jobs and having difficulty paying financing. The research aims to determine the differences in the financial performance of Islamic banks and conventional banks during the Covid-19 pandemic. This research also uses qualitative research with comparative descriptive objectives. The sample in this study consists of Shariah and conventional banks registered with the Financial Services Authority in 2020, totaling 62 banks, comprising 12 Shariah banks and 50 conventional banks. The analysis technique used is a difference test through independent sample t-test. The research results indicate that there is no difference in the financial performance of both Islamic and conventional banks. Financial performance, as assessed by CAR, NPL/NPF, and FDR/LDR ratios, still falls within the safe category, where banks can meet capital needs, maintain asset quality, and ensure bank liquidity during the Covid-19 pandemic. However, both Shariah and conventional banks have not been able to meet the BOPO and ROA ratio limits due to a decrease in bank income during the Covid-19 pandemic.